An overview of solar cell simulation tools - Abu Kowsar; Sumon Chandra Debnath; Md. Shafayet-Ul-Islam; Mohammad Jobayer Hossain; Mainul Hossain; AFM Kamal Chowdhury; Galib Hashmi; Syed Farid Uddin Farhad (Solar Energy Advances)
Solar cell simulation software offers an intuitive platform enabling researchers to efficiently model, simulate, analyze, and optimize photovoltaic devices and accelerate desired innovations in solar cell technologies. This paper systematically reviews the numerical techniques and algorithms behind major solar cell simulators reported in the literature. The status, scopes, and limitations of these simulators have been critically evaluated after recording their use in nearly two hundred published articles. For the first time, we present a comparative study of the simulators in terms of their availability, applications, and system requirements. We anticipate that this review will aid in selecting the most appropriate solar cell simulator for the numerical study of preferred type of solar cells.